2005
DOI: 10.1099/mic.0.27639-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of virulence plasmid gene expression defines three classes of effectors in the type III secretion system of Shigella flexneri

Abstract: Proteins directly involved in entry and dissemination of Shigella flexneri into epithelial cells are encoded by a virulence plasmid of 200 kb. A 30-kb region (designated the entry region) of this plasmid encodes components of a type III secretion (TTS) apparatus, substrates of this apparatus and their dedicated chaperones. During growth of bacteria in broth, expression of these genes is induced at 37 6C and the TTS apparatus is assembled in the bacterial envelope but is not active. Secretion is activated upon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
177
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(188 citation statements)
references
References 66 publications
11
177
0
Order By: Relevance
“…I B␣ degradation occurred after 1 h of infection of HeLa cells by the wild-type strain, probably because the increase in the number of intracellular bacteria overwhelmed the OspG protective effect, because there is no sustained production and delivery of OspG when bacteria are intracellular. Indeed, OspG production is tightly regulated by the TTS apparatus activity and controlled by MxiE (14), and transcription of MxiE-regulated genes is induced upon entry of bacteria into cells but repressed during multiplication of bacteria within epithelial cells (11). A role of OspG in interfering with activation of NF-B in vivo is supported by the observation that the inflammatory response induced upon infection of ileal loops by the ospG mutant was more severe than with the wild-type strain.…”
Section: Inactivation Of Ospg Increases the Inflammatory Response In mentioning
confidence: 54%
See 1 more Smart Citation
“…I B␣ degradation occurred after 1 h of infection of HeLa cells by the wild-type strain, probably because the increase in the number of intracellular bacteria overwhelmed the OspG protective effect, because there is no sustained production and delivery of OspG when bacteria are intracellular. Indeed, OspG production is tightly regulated by the TTS apparatus activity and controlled by MxiE (14), and transcription of MxiE-regulated genes is induced upon entry of bacteria into cells but repressed during multiplication of bacteria within epithelial cells (11). A role of OspG in interfering with activation of NF-B in vivo is supported by the observation that the inflammatory response induced upon infection of ileal loops by the ospG mutant was more severe than with the wild-type strain.…”
Section: Inactivation Of Ospg Increases the Inflammatory Response In mentioning
confidence: 54%
“…We present the functional analysis of the effector OspG, a 196-residue protein whose production is regulated by secretion activity (9,14). A two-hybrid screen in yeast and in vitro studies indicated that OspG binds ubiquitinylated E2s, including UbcH5.…”
mentioning
confidence: 99%
“…Contact of Shigella with host cells activates secretion by the injectisome and triggers transcription of ∼15 effector genes [22]. Expression of the effector genes is controlled by MxiE, an AraC-like transcriptional activator.…”
Section: Shigella Flexnerimentioning
confidence: 99%
“…Activation of transcription involves a regulatory cascade in which the product of the virF gene activates the downstream virB promoter . The VirB regulatory protein in turn alleviates H-NSmediated repression of the operons coding for the structural virulence genes (Adler et al, 1989;Le Gall et al, 2005;McKenna et al, 2003). VirB shows strong amino acid sequence homology to plasmid partitioning proteins such as ParB from plasmid/phage P1 and SopB from the F plasmid (Beloin et al, 2002).…”
Section: A Protein-independent Mechanismmentioning
confidence: 99%